The Effect of Compensation and Leadership on Employee Loyalty With Job Satisfaction as A Mediating Variable (A Case Study at PT Permodalan Nasional Madani, Solo Branch) - Ade Vebruanito Nistadi; Djoko Hanantijo (Institut Manajemen Wiyata Indonesia, 2026)
This study aims to analyze the influence of leadership and compensation on employee work loyalty at PT Permodalan Nasional Madani (PNM) Solo Branch, as well as the mediating role of job satisfaction in that relationship. Employee work loyalty is a strategic resource that significantly impacts the company’s competitive advantage. This study uses a quantitative approach, with data collected through surveys distributed to employees of PT PNM Solo Branch. The research population consists of 120 individuals, all of whom are treated as research respondents. Data collection was conducted through a questionnaire using a continuous rating scale (CRS) of 1–10 (Strongly Disagree—Strongly Agree). The data were processed using SmartPLS. The results of this study indicate that good compensation can improve job satisfaction, and good leadership can also improve job satisfaction. However, regardless of how good the compensation is, it cannot increase loyalty. In contrast, good leadership can increase loyalty. The higher the job satisfaction, the higher the loyalty. Job satisfaction can mediate and strengthen the relationship between compensation and loyalty, and it can also mediate and strengthen the relationship between leadership and loyalty